(untitled) (Bangladesh Journal of Child Health, 2012)
Objective: Identifying the risk factors of poor seizure control in children in a setting of tertiary care hospital. Design: Retrospective study. Setting: Child Development and Neurology Unit in the department of Paediatrics of Bangabandhu Sheikh Mujib Medical University (BSMMU). Study period: January 2004 through December 2005. Subjects: One hundred and twenty epileptic children were studied. They were grouped into controlled group (seizure free for more than six months) and poorly controlled group (having one or more seizure per month over a period of six months or more and who had experienced trials of at least two different antiepileptic drugs at optimum doses alone or in combination with adequate compliance) at the end of intervention and compared. Results: In this study 76 (63.3%) children were male and 44 (36.7%) children were female. Out of 120 cases 79 (65.8%) were in controlled group and 41 (34.2%) cases had poorly controlled epilepsy. Mean age of the controlled group and poorly controlled group of children were 79 months and 40.3 months respectively. Focal epilepsy was found in 30 (68%) cases in controlled and in 14 (31.8%) cases of poorly controlled group and generalized epilepsy was found in 42 (72%) cases in controlled and in 19 (28.8%) cases in poorly controlled group. Idiopathic epilepsy was more common which was 37 (46%) in controlled group against 14 (34%) in poorly controlled group. But symptomatic and cryptogenic cases were more prevalent with poorly controlled group 57.5% than controlled group 53%. In poorly controlled group 48.8% had cerebral palsy in comparison to 22.8% of controlled group. Early onset of seizure before one year was 25.3% in controlled and 78% in poorly controlled group (odds ratio=.2322, p =.0082) and one or more seizure per week 43% in controlled and 92.7% in poorly controlled group (odds ratio=.1218, p=.0032) were found as risk factors of poorly controlled epilepsy. Conclusion: Early onset of seizure before one year, symptomatic epilepsy and one or more seizure per week at diagnosis were found as risk factors of poorly controlled epilepsy in children attending a tertiary care hospital. DOI: http://dx.doi.org/10.3329/bjch.v34i2.10216 BJCH2010; 34(2): 44-50